UJI EFEK ANALGETIK EKSTRAK ETANOL DAUN PEPAYA (Carica papaya L) PADA MENCIT PUTIH JANTAN (Mus mucculus) - Octavianus, Stella (UNIVERSITAS SAM RATULANGI, 2014)
The objectives of this research were to find out analgesic effect of pepaya leaf etanol extract with concentration 0,6 g/kgBB, 1,2 g/kgBB and 2,4 g/kgBB on white male mouse (Mus musculus). The subject in this research were 15 white male mouse which divided into 5 groups, each group consist of 3 white male mouse. Negative control group were administered with CMC, positive control group were administered with mefenamid acid and experiment groups were administered with pepaya leaf etanol extract. Analgesic test were examined by giving pain stimulation to treated animals, such a 55°C heat stimulation. The response which observed were mouse licking feet or jumping response. The observation, then at 30, 60, 90 and 120 minutes after administered. The results shows that pepaya leaf etanol extract with concentration 0,6 g/kgBB, 1,2 g/kgBB and 2,4 g/kgBB prossess analgesic effect on white male mouse, expecially concentration 2,4 g/kgBB. It can be conclusion that pepaya leaf etanol extract own the analgesic effect on white male mouse thermal induction. Key words : analgesic, pepaya leaf extract, pain